The emerging therapeutic target of dynamic and reversible N6-methyladenosine modification during cancer development - Liu, Shougeng; Chen, Sihong; Tang, Chengfang; Zhao, Yingxi; Cui, Wei; Jia, Lina; Wang, Lihui (Frontiers in Oncology, 2022)
N6-Methyladenosine(m6a)modification as a reversible and dynamic epigenetic modification is ubiquitous in eukaryotic cells. The modification can alter the stability and function of base pairing and take part in RNA splicing, translocation, stability and translation into proteins to affect the fate of cells including the development of cancer. Evidence suggests that targeting m6A regulators play an essential role in tumor therapy, immunotherapy and multidrug resistance. However, at the current stage, many issues of m6A researchremains unclear. Here we review recent studies of m6A modifications in various aspects of tumor progression, tumor immunity, multidrug resistance and therapeutic targets for treatment to provide freshinsight for the further research of m6A methylation process.